The complete practitioner's guide to the bond market - Dym, Steven (McGraw-Hill, 2010)
The Complete Practitioner’s Guide to the Bond Market addresses the principles of the bond market and offers the tools to apply them in the real world. By tying the concepts of fixed-income products to big-picture aspects of the economy, this book prepares readers to apply specific tools and methods that will help them glean profits from the bond market.